VD_FINDINFO HC / 2025 / 792 vom 26. November 2025 - VD Tribunal cantonal (2025)
COMPÉTENCE RATIONE LOCI, DOMICILE, REVENU HYPOTHÉTIQUE, FORTUNE, REJET DE LA DEMANDE | 176 al. 1 CC, 46 LDIP, 79 al. 1 LDIP